2021
DOI: 10.1371/journal.pntd.0009910
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy in children in Cuba: Epidemiological and clinical description of 50 cases from 2012–2019

Abstract: Introduction In 1993, Cuba achieved leprosy elimination according to the World Health Organization’s (WHO) indicator of less than one case per 10,000 population. Despite this achievement, detection of new cases occurs every year among all age groups including children. Detection of new cases in children reveals persistent transmission of the infection. Objective To describe the clinical and epidemiological features of leprosy in individuals younger than 15 years (childhood leprosy) reported to the Cuban Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…Our result coincides with the study by kalita JM et al 5 In our study sex wise distribution on the type of leprosy was more in the lepromatous leprosy which was contradict to the sudy conducted by vaishist D et al 1wer e borderline tuberculoid was more.The study result shows that local group was more affected when comparing it to the migratory group, thereby our study shows that leprosy cases was found to be less in migratory group it coincides with their report on comparing to the study conducted by Samuel P et al 25 Disbailities among the leprosy patients indicates possible huge burden of morbidity among leprosy patients the study shows that 29% of cases were recorded with GRADE 1 disability and 11% were with GRADE 2 disability and followed by 60% of cases with no disability were found these reports were contradict with the study conducted by Shravani B et al, in which they have reported GRADE 2 disabilited was reported highly Shravani B et al 26 In this sudy the leprosy reactions were documented out of 35 cases in which 11% of the cases were found to be recorded with type 1 reactions and followed by 9% of type 2 reactions and 80% of no reaction cases were recorded. This was contradictory to the majority of the previous studies where type 2…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Our result coincides with the study by kalita JM et al 5 In our study sex wise distribution on the type of leprosy was more in the lepromatous leprosy which was contradict to the sudy conducted by vaishist D et al 1wer e borderline tuberculoid was more.The study result shows that local group was more affected when comparing it to the migratory group, thereby our study shows that leprosy cases was found to be less in migratory group it coincides with their report on comparing to the study conducted by Samuel P et al 25 Disbailities among the leprosy patients indicates possible huge burden of morbidity among leprosy patients the study shows that 29% of cases were recorded with GRADE 1 disability and 11% were with GRADE 2 disability and followed by 60% of cases with no disability were found these reports were contradict with the study conducted by Shravani B et al, in which they have reported GRADE 2 disabilited was reported highly Shravani B et al 26 In this sudy the leprosy reactions were documented out of 35 cases in which 11% of the cases were found to be recorded with type 1 reactions and followed by 9% of type 2 reactions and 80% of no reaction cases were recorded. This was contradictory to the majority of the previous studies where type 2…”
Section: Discussioncontrasting
confidence: 94%
“…1 Histiocytes, schwann cells, and melanocytes are among the target cells. 2 The main reasons of the delayed diagnosis have been identified as the extended incubation period and the tardy manifestation of the post-infection symptoms. Additionally, leprosy patients continue to face discrimination, prejudice, and shame in India.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 127,558 new leprosy cases were detected worldwide in 2020, a decrease of 37% compared to 2019, due to the implementation of the COVID-19 pandemic control programs ( 13 ). This is similar to what some authors have said that other public health priorities, such as the COVID-19 pandemic, pose a threat to the sustainability of surveillance and control efforts for diseases such as leprosy from a public health perspective ( 14 , 15 ).…”
Section: Introductionsupporting
confidence: 86%
“…However, despite its high specificity, the method has low sensitivity, especially in early cases, in paucibacillary cases and in cases of primary neural leprosy ( 18 ), which was the predominant form of cases in this study (71.4%). Retrospective studies on the diagnosis of pediatric cases observed positivity in the bacilloscopy method above 50% in Cuba ( 46 ) and 80% in Nepal ( 47 ), suggesting a concerning dependence on this technique for the diagnosis and detection of cases in more advanced stages in these countries, which have already declared the elimination of leprosy as a public health problem.…”
Section: Discussionmentioning
confidence: 99%